A Review of Topical Phage Therapy for Chronically Infected Wounds and Preparations for a Randomized Adaptive Clinical Trial Evaluating Topical Phage Therapy in Chronically Infected Diabetic Foot Ulcers - Christopher Anthony Duplessis; Biswajit Biswas (MDPI AG, 2020)
The advent and increasing prevalence of antimicrobial resistance commensurate with the absence of novel antibiotics on the horizon raises the specter of untreatable infections. Phages have been safely administered to thousands of patients exhibiting signals of efficacy in many experiencing infections refractory to antecedent antibiotics. Topical phage therapy may represent a convenient and efficacious treatment modality for chronic refractory infected cutaneous wounds spanning all classifications including venous stasis, burn-mediated, and diabetic ulcers. We will initially provide results from a systematic literature review of topical phage therapy used clinically in refractorily infected chronic wounds. We will then segue into a synopsis of the preparations for a forthcoming phase II a randomized placebo-controlled clinical trial assessing the therapeutic efficacy exploiting adjunctive personalized phage administration, delivered topically, intravenously (IV) and via a combination of both modalities (IV + topical) in the treatment of infected diabetic foot ulcers (perhaps the canonical paradigm representing complicated recalcitrant infected cutaneous wounds).